Climate change impacts on zooplankton and benthic communities in Lake Unterer Giglachsee (Niedere Tauern Alps, Austria). Issue 2 (2nd May 2013) - Luoto, Tomi P.; Nevalainen, Liisa
Abstract We examined a sediment core from a climatically sensitive High Alpine lake Unterer Giglachsee in the Niedere Tauern Alps in Austria. Our aim was to investigate long‐term climate change impacts on aquatic invertebrates (Chironomidae, Cladocera) with a special focus on the ending of the Little Ice Age and the present climate warming. Although the changes in faunal assemblages were relatively subtle through the sedimentary record, a mutual faunal breakpoint at ∼1900 AD was distinguished. In addition, the faunal dynamics correlated closely with instrumental Alpine temperature records and with reconstructed Northern Hemisphere climate development over the examined time period. In particular, significant relationships between relative taxa abundance and temperature were found with chironomids Sergentia, Paracladius, Paratanytarsus austriacus‐type, Cricotopus (I.) intersectus‐type, and Cricotopus cylindraceus‐type and with cladocerans Daphnia and Alonella excisa. Our results also suggested that the most recent assemblages represent unique community compositions. We conclude that our study lake is sensitive to climate warming and the composition of the aquatic ecosystem in Unterer Giglachsee has changed due to the impact of increasing temperatures. We predict that the further increasing temperatures will have direct but also cascading effects on the sensitive lake, potentially causing an ecosystem turnover where the key taxon Paracladius may play an important role.